Empowering Gig Workers: The Role of Self-Leadership and Islamic Work Ethics through Work Engagement - Ariawan, Muhammad Ghufron; Zulaikha, Siti (Jurnal Ekonomi Syariah Teori dan Terapan, 2025)
This study investigates the relationship between self leadership, Islamic work ethic, work motivation, and job performance with the mediation of work engagement and moderation of perceived organizational support in gig workers. The sample consisted of 240 Muslim online ojek drivers in Surabaya, aged 18-50 years, selected using purposive sampling. This quantitative research uses SEM-PLS method through SmartPLS4 application. The results show self leadership, Islamic work ethic, and work motivation have a significant positive influence on job performance. Work engagement acts as a significant mediator, while perceived organizational support weakens the relationship between self leadership and job performance. The limitation of the study is the limited scope of respondents in the online motorcycle taxi sector, so the results cannot be generalized to other gig workers. This study underscores the importance of strengthening work engagement and organizational support to improve the performance of gig workers, and highlights the relevance of Islamic work ethics in supporting job performance in the gig economy. This study has originality by examining the role of mediation and moderation in the relationship.